THE IMPLEMENTATION OF CRIMES EVIDENCE OF PREMEDITATED MURDER COMMITTED BY UNDERAGE CHILDREN - Meilisa Lydya; M Taufik Makarao; Slamet Riyanto (Fakultas Hukum, Universitas Islam As-Syafi'iyah, 2022)
The state of Indonesia is a state of law, when a child is in conflict with the law, the child faces public power which has the authority in the form of coercive measures that limit and even rob a number of children's rights in order to maintain public order. Children are gifts from God that must be protected and cared for according to their morals. The definition of a child in the Convention on the Rights of the Child which has been approved by the General Assembly on November 20, 1989, in Article 1 states that a child means every human being under the age of 18 (eighteen) years except under the law applicable to children. that maturity is reached more quickly. One of the cases that surfaced and became public attention was related to the crime of premeditated murder committed by minors, namely the case that occurred at the end of 2020 in the city of Bekasi. The perpetrator has been sentenced to 7 years in prison as stated in the decision of the Bekasi District Court Number 59/Pid.Sus-Anak/2020/PN Bekasi. Methods used: Normative juridical law research with analytical descriptive nature. Results of the study: The case started with hurt because previously Doni Saputra, who was the victim, forced to enter his genitals to Ahmad Yusuf, who was the defendant. But the defendant refused, but the defendant was threatened with a knife and the victim promised to give the defendant some money. However, because the amount of money continues to decrease and is often not paid, it creates feelings of resentment and hurt. Furthermore, on December 5, 2020, the perpetrator committed a murder which ended in the victim's death. Proof of elements of a criminal act of proof is planning to present evidence in the form of witness statements, letters, instructions for the defendant's testimony. The factor of the occurrence of the crime of murder committed by minors is caused by several factors, namely, factors within themselves (internal) and also factors around them (internal). Children commit the crime of murder because their emotional state is not stable and cannot control it properly and the child's lack of faith. Influences from outside the child such as the family who is not always there when needed, the weak economy and the circumstances of the surrounding environment also influence the child to commit the crime of murder. There are several factors that cause children to commit the crime of murder, namely: (1) Internal factors, namely emotional factors and religious factors, (2) external factors, namely family factors and environmental factors. Suggestion: for the community in particular parents should pay more attention to their children in the community environment so that unwanted things do not happen, especially murder cases, as parents must care for and protect children from the threat of crime that will befall them, in other words parents provide advice to children to be good children and not to commit crimes and to parents must provide sufficient education so that they can distinguish between good and bad.